The Effect of Sustainability Reporting Quality, Stock Return, Return on Asset, and BOPO on Earning Management Moderated by Net Interest Margin in Banking Companies Listed on The Indonesia Stock Exchange - Hendra; Murwaningsari, Etty (International Journal of Social and Management Studies, 2024)
At present, companies that care about environmental, social, and governance (ESG) are not only companies that are directly related to the environment, such as mining companies, but other companies that are far from being related to the environment are also becoming increasingly concerned about the Environment, Social, and Governance. The sample consists of Indonesian banking companies publicly traded on the Indonesian stock exchange. The overall sample size is 36 organizations, drawn from data spanning the years 2015 to 2022, and examined using Eviews. The goal of this study is to examine the association between variables related to the quality of ongoing reporting and corporate performance in banking businesses listed on the IDX, which are moderated by the Net Interest Margin (NIM) to Earnings Management (EM). The study's findings indicate that SRQ has a negative effect on earnings management (EM), Stock Return (SR) has a negative effect on earnings management (EM), Return on Assets (ROA) has no effect on earnings management (EM), Cost of Operations to Income Operations (BOPO) has a negative effect on earnings management (EM), and the Net Interest Margin (NIM) moderates the effect of Sustainability Reporting Quality (SRQ), Stock Return (SR), Return on Assets (ROA), and earnings management (EM).